Interactions between carnivore species: limited spatiotemporal partitioning between apex predator and smaller carnivores in a Mediterranean protected area - Ferretti F.; Oliveira R.; Rossa M.; Belardi I.; Pacini G.; Mugnai S.; Fattorini N.; Lazzeri L. (Frontiers in Zoology, 2023)
Background: There is need of information on ecological interactions that keystone species such as apex predators establish in ecosystems recently recolonised. Interactions among carnivore species have the potential to influence community-level processes, with consequences for ecosystem dynamics. Although avoidance of apex predators by smaller carnivores has been reported, there is increasing evidence that the potential for competitive-to-facilitative interactions is context-dependent. In a protected area recently recolonised by the wolf Canis lupus and hosting abundant wild prey (3 ungulate species, 20–30 individuals/km2, together), we used 5-year food habit analyses and 3-year camera trapping to (i) investigate the role of mesocarnivores (4 species) in the wolf diet; (ii) test for temporal, spatial, and fine-scale spatiotemporal association between mesocarnivores and the wolf. Results: Wolf diet was dominated by large herbivores (86% occurrences, N = 2201 scats), with mesocarnivores occurring in 2% scats. We collected 12,808 carnivore detections over > 19,000 camera trapping days. We found substantial (i.e., generally ≥ 0.75, 0–1 scale) temporal overlap between mesocarnivores—in particular red fox—and the wolf, with no support for negative temporal or spatial associations between mesocarnivore and wolf detection rates. All the species were nocturnal/crepuscular and results suggested a minor role of human activity in modifying interspecific spatiotemporal partitioning. Conclusions: Results suggest that the local great availability of large prey to wolves limited negative interactions towards smaller carnivores, thus reducing the potential for spatiotemporal avoidance. Our study emphasises that avoidance patterns leading to substantial spatiotemporal partitioning are not ubiquitous in carnivore guilds.